Combined foliar and soil selenium fertilizer increased the grain yield, quality, total se, and organic Se content in naked oats. (July 2021) - Li, Junhui; Yang, Wenping; Guo, Anna; Qi, Zewei; Chen, Jie; Huang, Tingmiao; Yang, Zhenping; Gao, Zhiqiang; Sun, Min; Wang, Jianwu
Abstract: Background: Naked oat ( Avena nuda L.) is one of the most important, nutritionally rich grain crops produced worldwide. To determine the most reasonable selenium (Se) application method for naked oat, field experiments were conducted in the Loess Plateau from 2017 to 2018 to investigate the effects of Se fertilizer on grain yield, quality, Se content, and forms using a randomized block design with four treatments: foliar Se fertilizer application (S), soil Se fertilizer application (T), combined foliar and soil Se fertilizer application (TS), and control (CK) with no Se fertilizer. Results: Compared to CK, the grain yield and Se content under the Se fertilizer treatments increased by 4.86–10.04% and 72.5–203.08%, respectively. Se forms of naked oat grains in T, S, and TS were mainly selenomethionine (SeMet). The SeMet content average increased by 45.69% (T), 53.75% (TS), and 51.19% (S), and the SeCys (selenocysteine) content increased by 90.73% (TS) and 75.43% (S), the Se fertilizer treatment increased the Se content in the roots, stems, leaves, and ears of oats. TS treatment, the Se content in ears was the highest. Se application significantly affected the crude protein and crude ash contents with the maximum recorded value observed in TS. Moreover, TS had significantly higher content of globulin, glutenin, and lysine, leucine, cystine, glutamic acid, and total amino acid contents for two consecutive years ( P  < 0.05). Se application significantly affected the iron (Fe), zinc (Zn), and calcium (Ca) contents ( P  < 0.05) with the Ca and Zn contents in the seeds reaching the maximum recorded values in TS. Conclusions: Based on these findings, combined foliar and soil Se fertilizer was determined to be the best Se application method on naked oats. Graphical abstract: Image 1 Highlights: The contents of Fe, Ca and Zn were greatly affected by Se supplementation. The application of exogenous Se increased naked oat yield. The proportion of organic Se in oat grain increased after Se supplementation. Oat grain quality varied due to the different Se application method. Combined foliar and soil Se was the best Se application method for naked oats.